Direct medical expenditures associated with Alzheimer's and related dementias (ADRD) in a nationally representative sample of older adults – an excess cost approach. (4th May 2018) - Deb, Arijita; Sambamoorthi, Usha; Thornton, James Douglas; Schreurs, Bernard; Innes, Kim
ABSTRACT: Objective: To estimate the excess direct annual healthcare expenditures associated with Alzheimer's and related dementias(ADRD) among community-dwelling older adults in the United States. Methods: This retrospective cross-sectional study compared the annual healthcare expenditures between elderly individuals aged 65 years and older with ADRD ( n = 662) and without ADRD ( n = 13, 398) using data from the Medical Expenditure Panel Survey (MEPS) for the years 2007, 2009, 2011 and 2013. Adjusted total annual medical expenditures was estimated using generalized linear model with gamma distribution and log link in 2013 U.S. dollars. Adjusted inpatient, outpatient, emergency, home healthcare and prescription drug expenditures, were estimated using two-part logit-generalized linear regression models. Results: The adjusted mean total healthcare expenditures were higher for the ADRD group as compared to the no ADRD group($14, 508 vs. $10, 096). Among those with ADRD, 34.3% of the expenditures were for home healthcare as compared to 4.4% among those without ADRD. Among users, the ADRD group had significantly higher home healthcare ($3, 240 vs. $566) and prescription drug expenditures($3, 471 vs. $2, 471). There were no statistically significant differences in inpatient, emergency room and outpatient expenditures between the ADRD and no ADRD group. Conclusion: ADRD in U.S. community-dwelling elders is associated with significant financial burden, primarily driven by increased home healthcare use.